Perancangan Sistem Informasi Pencatatan dan Pembayaran Iuran Warga Berbasis Web Pada Lingkungan RT 002 RW 006 Kelurahan Cipayung - Pragata Azis Pratama; Farizi Ilham; Arum Cahyaning Tyas; Muhammad Adityo Darmawan (BINER : Jurnal Ilmu Komputer, Teknik dan Multimedia, 2026)
Rukun Tetangga (RT) 02 RW 06 Kelurahan Cipayung is a community service unit overseeing approximately 120 Heads of Households (KK). In its daily operations, the process of recording and paying residents' dues is still conducted manually using cash books and physical archives. This frequently leads to various issues such as the risk of recording errors, data vulnerability to damage or loss, and a lack of information transparency regarding payment status and the use of funds for residents. This research aims to design and build a web-based information system for recording and paying residents' dues to improve administrative efficiency, data security, and information disclosure. The system development method used is the System Development Life Cycle (SDLC) with the Waterfall model, which includes the stages of requirement analysis, design, implementation, testing, and maintenance. Data collection was conducted through interviews with the RT Chairperson and direct observation of the existing workflow. The developed system features Role-Based Access Control (RBAC) authentication, a dues transparency dashboard, a digital payment module through uploading transfer proofs, and automated financial recapitulation reports. This system is expected to help RT management become more effective, transparent, and accountable in managing residents' dues.